A comparison of implementation of linear and nonlinear constitutive models in numerical analysis of layered flexible pavement - Ghadimi, Behzad; Nikraz, Hamid (2016)
It is generally accepted among pavement engineers that the granular layers in flexible pavement behave in a nonlinear mechanical way. Existing literature documents different constitutive equations to model this nonlinearity. This paper compares four well-known constitutive models: linear elastic, K−θ, Uzan–Witczak and Lade–Nelson. In the first stages of numerical simulation, three static linear elastic models were constructed in CIRCLY, KENLAYER and ABAQUS and the results of the analysis were compared with one another. Following this, three-dimensional models were constructed in ABAQUS, and the four constitutive models were implemented for use in the finite-element model. Three sets of material parameters were considered for the analysis. The results calculated from each model were presented and compared and consisted of the following: surface deflection under loading wheels, tensile strain at the bottom of an asphalt layer, and vertical strain and vertical stress at the top of the subgrade layers. The development of the elastic modulus and vertical stress in the base layer was also investigated and the contours of the vertical elastic modulus are presented.